Species Compotition of Fruit Bats (Pteropodidae) in Institut Teknologi Sumatera, Lampung - Hasibuan, Mhd Muhajir; Fitria Ningsih, Desvita; Vincent, Joy; Maulana, Sena; Sari, Nurika Arum; Alfajrin, Achmad Chalid; Dwiputra, Mohammad Ashari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Fruit bats (family Pteropodidae) pollinate around 300 species of tropical plants of high economic value over a wide range of areas. This large role does not match the status of their population, which continues to decline due to habitat loss, particularly in urban areas. The Sumatra Institute of Technology (ITERA) campus, which is currently under development, may result in habitat changes that may affect bats. These concerns have led to the need for research into bat diversity on the ITERA campus. The result could be utilised to monitor and develop the environmental management of the campus. The research was conducted from May to September 2023 in five different habitat types. Data were collected using 3 mistnets and 3 night repetition each habitat. The data were analysed using indices of diversity, evenness and species richness. The study recorded 143 individuals of 7 species. The highest number of species and diversity was observed in the sengon and rubber habitat (6 species). The lowest number of species and diversity was found in the botanical garden (2 species).